Kompetensi Kepemimpinan Guru Pendidikan Agama Katolik dalam Menciptakan Lingkungan Belajar yang Kondusif di Smp Negeri 4 Nubatukan - Novianti Gobay; Yoseb Belen Keban; Alfonsus Mudi Aran (CV. ALIM'SPUBLISHING, 2026)
This study aims to determine the leadership competency of Catholic religious education teachers in creating a conducive learning environment at SMP Negeri 4 Nubatukan. This research used a qualitative approach with a case study approach. Data collection was conducted through observation, interviews, and documentation involving Catholic religious education teachers, students, and school officials. The results indicate that Catholic religious education teachers have demonstrated leadership competency through their ability to manage the classroom, provide good role models, build positive relationships with students, and provide motivation during the learning process. Teachers also strive to create a safe, comfortable, and orderly learning environment to encourage students to be more active in learning. Furthermore, several supporting factors exist, such as collaboration between teachers and the school, parental support, and the application of religious values ​​in the school environment. However, this study also identified several obstacles, such as limited learning facilities, lack of student participation, and limited learning time. Based on the results, it can be concluded that the leadership competency of Catholic religious education teachers plays a crucial role in creating a conducive learning environment and supporting student development, both academically and spiritually.